Pension reform in Belarus in the shadow of social Europe: Vulnerability issues of people aged 50+ and points for improvement - Sierž Naūrodski (Center for Social and Economic Research (CASE), 2016)
The policy brief presents a review of potential effects of parametric pension reform in Belarus starting in 2017 for the population aged 50 and more in terms of unemployment, alcohol consumption, and poverty. It concludes that, despite the fact that raising the retirement age is overdue in Belarus to address demographic challenges, it may have a negative impact on the quality of life of people close to retirement age as well as a poorer GDP effect within current conditions on the labor market in Belarus. The paper presents a set of public policy improvement directions in Belarus, which could help mitigating vulnerability of the group 50+ during the pension reform.
Keywords: H53; H55; J14; J26; 330; Belarus; parametric pension reform; pre-retirement population vulnerability; 50+; social security; policy in transition countries